Characterizing healthcare utilization patterns in a Danish population with headache: results from the nationwide headache in Denmark (HINDER) panel - Thien Phu Do; Mikala Dømgaard; Simon Stefansen; Timothy J. Steiner; Messoud Ashina (The Journal of Headache and Pain, 2023)
Abstract Introduction Worldwide, far from all of those who would benefit make use of headache services, largely because of clinical, social, and political barriers to access. Identifying the factors contributing to low healthcare utilization can generate evidence to guide health policy. Our purpose here is better to characterize healthcare utilization patterns in Denmark. Methods The Headache in Denmark (HINDER) study is a nationwide cross-sectional survey of people with headache, conducted using SurveyXact (Rambøll Group A/S, Copenhagen). Healthcare utilization was assessed in a study sample generated by population screening and recruitment. Data collection occurred over two weeks, from September 23rd until October 4th, 2021. The questions enquired into disease characteristics, management, burden, medication intake and healthcare utilization. Results The number of participants included in the HINDER panel was 4,431, with 2,990 (67.5%: 2,522 [84.3%] female, 468 [15.7%] male; mean age 40.9 ± 11.6 years) completing the survey. One quarter of participants (27.7%) disagreed or strongly disagreed that they were able to manage their headache attacks. Most participants (81.7%) agreed or strongly agreed that their headache was a burden in their everyday lives. The most reported acute medications, by 87.2% of participants, were simple analgesics; of note, 8.6% reported using opioids for their headache. One quarter of participants (24.4%) had never consulted a medical doctor for their headache; one in six (16.5%: more than two thirds of the 24.4%) had never done so despite agreeing or strongly agreeing that their headache was a burden in their everyday lives. Two thirds (65.3%) of participants overall, and almost three quarters (72.4%) of those with weekly headache, had tried one or more complementary or alternative therapies outside conventional medical care. Conclusions Our findings are indicative of inadequate delivery of headache care in a country that provides free and universal coverage for all its residents. The implications are twofold. First, it is not sufficient merely to make services available: public education and increased awareness are necessary to encourage uptake by those who would benefit. Second, educational interventions in both pre- and postgraduate settings are necessary, but a prerequisite for these is a resetting of policy priorities, properly to reflect the very high population ill-health burden of headache.